Evaluation of the effects of photodynamic therapy with hypericin-glucamine in the treatment of periodontal disease induced in rats - Macedo, Paula Delello [UNESP] (2018)
Purpose: The purpose of this study was to evaluate the effectiveness of a photosensitizer hypericin-glucamine, activated by LED amber (34.10 J/cm2) as an adjuvant to scaling and root planing (SRP), on the treatment of experimental periodontal disease (PD) in rats. Methods: In a 15-day period, PD was induced in the mandibular molars through ligature placement. The animals (n = 60) were randomly divided into four groups: control (with induction of periodontal disease), scaling and root planing (SRP), antimicrobial photodynamic therapy (aPDT), and SRP + aPDT. At 7, 15, and 30 days after treatments, animals were euthanized. Digital microtomography, histometric, and stereometric analyses were performed to calculate the bone loss of mandibular second molars, and the tissue repair was analyzed histologically. The data were subjected to statistical analysis (α = 5%). Results: Histologically, the control group periodontium showed several morphological changes, but an evident gradual reduction in the inflammatory process was observed in the subsequent periods. The SRP, aPDT, and SRP + aPDT groups presented the same, but in less intensity. The stereometric analysis showed a significantly higher proportion of fibroblasts in SRP group (p < 0,001) and SRP + aPDT group (p < 0.0001) compared to that in the control group at 7 days post treatment. Conclusions: We conclude that scaling and root planing with or without photodynamic therapy with hypericin-glucamine increased density of the fibroblast and cell density. However, there is no statistically significant difference between SRP and SRP + aPDT.